The intersection of stress, loneliness, and mental health attitudes in young multinational corporation employees - Thuy Thi Thanh LE; Ha-Chau TRAN-NGOC; Van-Nhi HO; Bao-Nhu NGUYEN-HOANG; Hoang-Anh Ngoc HO; Van-Anh TRAN-DO (Journal of Health and Social Sciences, 2025)
Introduction: Promoting psychological well-being in young multinational corporation (MNC) employees requires understanding the relationship between stress, loneliness, and mental health attitudes. However, existing research lacks a comprehensive analysis of how these factors interact and influence attitudes toward seeking psychological help. Addressing this gap is crucial for developing effective workplace mental health interventions. Methods: Using a sample of 118 young MNC employees in Vietnam (64.4% Gen Z, 81.4% female, 11% LGBTQ+, 67.8% single), this study examines relationships between stress, loneliness, problematic internet use (PIU), and attitudes toward seeking psychological help, with tenure and remote work status as moderators. Data were analyzed using partial least squares structural equation modeling (PLS-SEM). Results: Perceived stress is positively correlated with problematic internet use (PIU) and dissatisfaction with social relationships, while negatively correlated with social satisfaction. PLS-SEM revealed that perceived stress significantly predicted dissatisfaction with social relationships (β = 0.408, p < 0.001), which was strongly associated with PIU (β = 0.407, p < 0.001), indicating a maladaptive coping mechanism. Higher social dissatisfaction correlated with negative attitudes toward psychological help. Longer tenure was associated with reduced social dissatisfaction, whereas remote work intensified the loneliness–PIU relationship. Tenure (β = -0.209, p < 0.05) and remote work status (β = 0.216, p < 0.05) moderated the stress–loneliness and loneliness–PIU relationships, respectively. Conclusion: These findings highlight the complex relationship between stress, loneliness, and workplace factors in young MNC workers. Addressing problematic internet use and improving psychological support may reduce stress and loneliness. Furthermore, tenure-related interventions could foster social well-being in corporate environments, emphasizing the need for targeted workplace mental health strategies.